2021
DOI: 10.1186/s12884-021-03665-0
|View full text |Cite
|
Sign up to set email alerts
|

Stressors, coping, and resources needed during the COVID-19 pandemic in a sample of perinatal women

Abstract: Background Psychological stress and coping experienced during pregnancy can have important effects on maternal and infant health, which can also vary by race, ethnicity, and socioeconomic status. Therefore, we assessed stressors, coping behaviors, and resources needed in relation to the COVID-19 pandemic in a sample of 162 perinatal (125 pregnant and 37 postpartum) women in the United States. Methods A mixed-methods study captured quantitative resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
80
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(99 citation statements)
references
References 32 publications
11
80
0
1
Order By: Relevance
“…Several studies have now looked at the experiences of pregnant and postnatal women globally, and while their experiences are specific to their location and the timeframe in the pandemic that the research was carried out, recurrent themes are emerging. As with the women in our study, anxiety and fear [ 14 , 20 24 ] were commonly reported as was the need for reliable information [ 22 24 ]. In one study of perinatal anxiety in the USA, 60% of women reported moderate or severe anxiety symptoms [ 25 ].…”
Section: Discussionmentioning
confidence: 70%
“…Several studies have now looked at the experiences of pregnant and postnatal women globally, and while their experiences are specific to their location and the timeframe in the pandemic that the research was carried out, recurrent themes are emerging. As with the women in our study, anxiety and fear [ 14 , 20 24 ] were commonly reported as was the need for reliable information [ 22 24 ]. In one study of perinatal anxiety in the USA, 60% of women reported moderate or severe anxiety symptoms [ 25 ].…”
Section: Discussionmentioning
confidence: 70%
“…Stressors that are unique to COVID-19 – such as worries about being unprepared for birth due to the pandemic - were found to predict increased anxiety among pregnant women during the pandemic ( Preis et al, 2020b ). Other COVID-19 related stressors (food scarcity, loss of income, loss of childcare, tension in the home) may put inordinate stress on parents ( Barbosa-Leiker et al, 2021 ; Boekhurst et al, 2021; Moyer et al 2020 ). These reports, as well as the known adverse effects of stress on perinatal outcomes ( Woods et al, 2010 ; Ibrahim & Lobel, 2020 ), highlight the critical need to understand how the pandemic may be affecting the wellbeing of perinatal women and their offspring.…”
Section: Introductionmentioning
confidence: 99%
“…Qualitative methodology can be helpful for this type of inquiry. Some prior studies have utilized qualitative and mixed methods to examine perinatal women's experiences during the pandemic, yet these studies have focused upon community samples ( Barbosa-Leiker et al, 2021 ; Farewell et al, 2020 ; Moyer et al, 2020 ) and provide less information about women with histories of depression. Understanding how women with depression histories cope in the context of a significant public health emergency is critical, given the particular risks of depressed individuals engaging in social withdrawal and isolation ( Kupferberg et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…This is likely to have led to an over-representation of White women and those who are higher in socioeconomic status (higher incomes and educational levels). Caution must be taken in the generalizability of our findings to all pregnant women in the U.S., particularly given the disparities faced by racial/ethnic minorities and those of lower socioeconomic status throughout the pandemic [ 5 , 42 ]. Disparities regarding how stress and mental health are discussed between providers and patients within prenatal care settings have existed prior to the pandemic [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…In spite of these limitations, our work draws attention to understanding the prenatal distress experiences during the COVID-19 pandemic, highlighting the nuances of distress from current conditions. Our findings suggest that under the conditions of the pandemic, women who experience prenatal distress might benefit from the introduction of interventions that address distress tolerance such as mindfulness-based or relaxation therapy [ 42 ] and supports that help to cover responsibilities or provide financial assistance. Providers are encouraged to speak to patients about their mood [ 43 ], to inquire with their patients whether they have such support, and to consult with social work or other specialists to determine if there are ways to meet the tangible needs of pregnant women.…”
Section: Discussionmentioning
confidence: 99%